Comparison of primary and stem cell-derived osteoblasts and the influence of nanoscale mechanotransduction on cell behaviour - Hollingworth, Mathew (2019)
The use of stem cells in regenerative bone strategies holds great promise, however it is becoming increasingly clear that stem cell-derived osteoblasts differ in behaviour and function to native osteoblasts. Pluripotent embryonic stem cells (ESCs) present a useful model to study developmental biology and in particular, osteogenesis in vitro; information which can be used to further inform and develop regenerative strategies for bone repair. Here, the differentiation of ESCs is compared to primary calvarial osteoblasts. Whilst both cell types exhibit mineralisation, expression of bone specific proteins and increased ALP activity, marked differences are observed in these characteristics over 35 days, particularly in mineral formation.